2020
DOI: 10.1038/s41598-020-77243-3
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning to predict mortality after rehabilitation among patients with severe stroke

Abstract: Stroke is among the leading causes of death and disability worldwide. Approximately 20–25% of stroke survivors present severe disability, which is associated with increased mortality risk. Prognostication is inherent in the process of clinical decision-making. Machine learning (ML) methods have gained increasing popularity in the setting of biomedical research. The aim of this study was twofold: assessing the performance of ML tree-based algorithms for predicting three-year mortality model in 1207 stroke patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…Several tools can be used to perform ML analyses: Tougui et al performed a study on these tools in the context of heart disease classification [41] and identified Knime analytics platform as the best tool in terms of data manipulation, creating complex workflows, parameter tuning, and control of the algorithms. Moreover, this tool has already been used to perform biomedical studies also in fields such as ophthalmology and signal processing [42][43][44], and in cardiology [45,46].…”
Section: Machine Learning: Tool and Algorithmsmentioning
confidence: 99%
“…Several tools can be used to perform ML analyses: Tougui et al performed a study on these tools in the context of heart disease classification [41] and identified Knime analytics platform as the best tool in terms of data manipulation, creating complex workflows, parameter tuning, and control of the algorithms. Moreover, this tool has already been used to perform biomedical studies also in fields such as ophthalmology and signal processing [42][43][44], and in cardiology [45,46].…”
Section: Machine Learning: Tool and Algorithmsmentioning
confidence: 99%
“…Stroke is the second most common cause of death and disability worldwide. [1][2][3] Globally, there were 80.1 million prevalent cases of stroke, with 84.4% ischemic stroke (IS). 4 In 2016, 5.5 million died of stroke, and IS accounted for 49.1% of all stroke deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The generalization was unsatisfied under the mismatched testing condition. The possible reasons were as follows: (1) The limited sample size of the recruited subjects (n = 29) hindered the model's effective generalization, i.e., recognizing completely new inputs, compared to those achieved this in the literatures usually with larger sample sizes (e.g., n > 100) (Kim et al, 2020;Scrutinio et al, 2020).…”
Section: Mapping the Semg Data To Masmentioning
confidence: 99%